2017
DOI: 10.5860/crl.v78i3.16591
|View full text |Cite
|
Sign up to set email alerts
|

The Internationalization of the Academic Library: A Systematic Review of 25 Years of Literature on International Students

Abstract: This study is a systematic review of the library and information science (LIS) literature related to international students and academic libraries. A systematic review involves the methodical collection and analysis of a body of literature and is growing in popularity in the LIS field. Three wellknown LIS databases were systematically searched for articles related to the topic, and manual bibliography searches were conducted to find additional publications. Journal articles, book chapters, and conference paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…These well-known indexing and abstracting databases in the field of LIS provide extensive coverage of journals in the field. The same databases were used in previous studies as data sources for evaluating the research output of LIS authors (Click, Wiley &Houlihan 2017, Fourie, Bitso andBothma 2014). Vinson and Welsh (2014) argued that LISTA had the broadest range of coverage and is a logical choice for libraries that can only afford a subscription to a single LIS database.…”
Section: Methodsmentioning
confidence: 99%
“…These well-known indexing and abstracting databases in the field of LIS provide extensive coverage of journals in the field. The same databases were used in previous studies as data sources for evaluating the research output of LIS authors (Click, Wiley &Houlihan 2017, Fourie, Bitso andBothma 2014). Vinson and Welsh (2014) argued that LISTA had the broadest range of coverage and is a logical choice for libraries that can only afford a subscription to a single LIS database.…”
Section: Methodsmentioning
confidence: 99%
“…A recent survey of the last 25 years of library literature offers an in-depth look at the many different ways that international students have been studied in libraries (Click, Wiley, & Houlihan, 2017). The growing number of library studies devoted to international students seems to signal a surging interest by librarians in learning how to better understand and work with this important student user group on campus.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research about language in libraries exists in the literature and can be found as a topic associated with populations like international students 27 and immigrants. 28 Considering the complexity of the relationship between language and information, very few studies…”
Section: Language In Librariesmentioning
confidence: 99%